BOOSTING LUXCRIME SALES: TIKTOK MARKETING CONTENT'S IMPACT ON IMPULSE BUYING WITH PRODUCT REVIEWS MODERATION - Isman, Syahvina Bianca; Maulidizen, Ahmad (Universitas Nusa Cendana, 2024)
This research aims to investigate the impact of TikTok marketing content on impulsive purchasing moderated by product reviews, focusing on cosmetic products with the highest sales in Indonesia, specifically Luxcrime as the brand under study. The research method employed is quantitative research involving 100 respondent samples. Data management was conducted using Smart-PLS 4.0. The findings reveal that, without considering the contribution of the moderating variable, TikTok marketing content significantly influences impulsive purchasing. However, when considering the moderating effect of product reviews, TikTok marketing content does not significantly affect impulsive purchasing. The study also found that TikTok marketing content and product reviews collectively explain 40.9% of the variance in impulsive purchasing behavior. In conclusion, impulsive purchasing of Luxcrime cosmetic products can be significantly influenced by TikTok marketing content. Furthermore, product reviews were found to not significantly influence TikTok marketing content and impulsive purchasing when serving as a moderating variable, but they may have a significant impact on TikTok marketing content when acting as an independent variable Keywords: TikTok Marketing; Impulsive Purchasing; Cosmetic Products; Luxcrime; Product Review